The problem of occurrence of faulty postures in children and adolescents in the city of Zielona Góra and the region - Permoda, Anna; Permoda, Andrzej; Chudak, Bożena (Polish Journal of Public Health, 2010)
Introduction. In recent years in Poland the number of children and adolescents afflicted with faulty posture has highly increased. This is mostly caused by poor life-style and bad motor habits. These factors evoke a chain reaction in the human body which leads to consolidation of various defects and this may result in the development of discopathy and many other health problems. Too late diagnosis of faulty posture or disregard of minor posture abnormalities contribute to the increase of faulty posture occurrence. Early detection of abnormalities and correct rehabilitation can break the pathological cause-and-effect process. Aim. The aim of the study was to assess the frequency of faulty posture in different body planes and the contracture of the hamstring muscles among school-age children in the region of Zielona Góra. Material and methods. The study encompassed primary school children in the city of Zielona Góra and the region. Altogether 7,781 persons (3,890 girls and 3,891 boys) were examined. Every person was subjected to the finger-floor test, the Adams test, the pelvic static test, Bertrand’s test and the visual body posture assessment of the frontal, sagittal and transverse planes. The results of the research have been presented in the form of figures and percentage. Results. The study revealed disorders in body posture in 77% of the examined persons. Most faulty posture cases are observed in 6- and 7-year-old children.